Enterohemorrhagic Escherichia coli (EHEC) Strains of Serogroup O118 Display Three Distinctive Clonal Groups of EHEC Pathogens - Wieler, Lothar H. (American Society for Microbiology, 2000)
A recent case report of a child infected with enterohemorrhagic Escherichia coli (EHEC) of serotype O118:H16 in Bavaria, in association with the isolation of a bovine O118 strain on the same farm (A. Weber, H. Klie, H. Richter, P. Gallien, M. Timm, and K. W. Perlberg, Berl. Muench. Tieraerztl. Wochenschr. 110:211–213, 1997), prompted us to investigate the relationship between bovine and human strains of serogroup O118. A total of 29 human O118 E. coli strains from Europe (21), Canada (4), and Peru (4) were compared by virulence typing and macrorestriction analysis with 7 bovine O118 EHEC strains isolated in Bavaria. Twenty-five of the human strains were characterized as EHEC. By serotyping and determination of the virulence-associated factors Shiga toxin (stx1 stx2 stx2 variants), intimin (eae), and EHEC hemolysin (Hly(EHEC)), three distinctive groups of O118 human pathogens were identified. Most of the strains belonged to serotype O118:H16, displaying the virulence traits Stx1, intimin, Hly(EHEC), and EspP/PssA (group 1). In addition, we identified strains of serotype O118:H12 (Stx2d only; group 2) and of serotype O118:H30 (Stx2 and intimin; group 3). Macrorestriction analysis with BlnI and XbaI revealed that all strains with a single O118 serotype profile (O118:H12, O118:H16, and O118:H30) belonged to one clonal cluster, irrespective of their origin. Group 1 strains clustered in the same clonal group as the bovine O118:H16 strains. Moreover, four pairs of strains of different origins and indistinguishable by all other methods applied were identified as group 1 strains. Our data support the direct transmission of an EHEC O118:H16 strain from a calf to a 2-year-old boy in the above-mentioned case report. Since bovine and human O118:H16 strains represent the same clones, they must be considered zoonotic EHEC pathogens. In contrast, EHEC strains of serotypes O118:H12 and O118:H30 have been isolated only from humans, indicating a reservoir for certain human O118 EHEC strains other than bovines.